Program Pembentukan Kader Cilik sebagai Upaya Peningkatan Pelayanan Kesehatan Berbasis Masyarakat Kelurahan Melebung - Soraya Medina Ruza; Arnila Melina; Ami Amelia; Zulhendri Zulhendri; Arzita Diandra Diva Fadhilla; Rizka Prasetya; Fatimah Azzahra; Muhammad Naufal Makarim (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The "Kader Cilik" program in Kelurahan Melebung is an initiative aimed at improving community-based health services. This program focuses on training children to become young health leaders with basic skills to promote health and engage in preventive and promotive efforts within their communities. The children are expected to become change agents who can educate their families, peers, and local communities on the importance of maintaining clean and healthy living behaviors. The success of the program will be measured by changes in community health behaviors, a reduction in preventable diseases, and an overall improvement in the quality of life. By involving children as "Kader Cilik," the program aims to create long-term change starting with the younger generation, building a more health-conscious community from an early age.